2004
DOI: 10.1002/we.109
|View full text |Cite
|
Sign up to set email alerts
|

Smoothing effects of distributed wind turbines. Part 1. Coherence and smoothing effects at a wind farm

Abstract: Recently there has been a marked increase in wind power generation. From a power system point of view, because a wind turbine is an intermittent generator with large output fluctuation, any increase in the number of wind turbines gives rise to concerns about the adverse effects of wind turbines on power quality. The smoothing effects of wind turbine output fluctuation are of great importance in assessing the impacts of a large number of wind turbines. This article examines smoothing effects at a wind farm. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 7 publications
2
42
0
2
Order By: Relevance
“…The histogram of steps ( Figure 5) indicates that some damping of the higher magnitude fluctuations (above about 20% of nameplate capacity) occurs (Figure 5b), as previously observed for wind power output. 8,9 We caution that these data are 10-min samples, and that one array (Prescott) has twice the peak power output either of the other two. Samples at …”
Section: Geographic Correlation and Step Size Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The histogram of steps ( Figure 5) indicates that some damping of the higher magnitude fluctuations (above about 20% of nameplate capacity) occurs (Figure 5b), as previously observed for wind power output. 8,9 We caution that these data are 10-min samples, and that one array (Prescott) has twice the peak power output either of the other two. Samples at …”
Section: Geographic Correlation and Step Size Analysismentioning
confidence: 99%
“…The power spectrum for a single APS site is very similar to that from the three combined sites (Figure 9). For wind, Nanahara et al 8 report smoothing when combining output from six turbines relative to a single turbine as a change in the slope of the power spectrum; they report an attenuation of the magnitude of fluctuations of frequencies above $1Á0 Â 10 À3 Hz. The available data for the present study limit our observations to frequencies below 8Á3 Â 10 À4 Hz, but it appears from the spectral analysis that fluctuations slower than this frequency (20 min) and faster than $2 Â 10 À5 Hz (14 h) are not significantly diminished due to site diversity over several hundred km.…”
Section: Power Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [9] demonstrated an 87% reduction in wind power variability by interconnecting four WFs, and that interconnecting 16 more WFs only gave 8% additional reduction. In [10,11], smoothing effects in a hypothetical WF and coherence between distant turbines were investigated via PSD, by using real measurements of wind speeds in Japan. A new index to quantify smoothing effects of wind power was proposed in [11], and the results from applying it indicated non-significant smoothing effects for periods longer than 100 min, for WFs located hundreds of kilometers apart.…”
Section: Introductionmentioning
confidence: 99%
“…spatial patterns oscillating with single frequencies for all observables (wind powers at hypothetical WFs in this paper). By utilizing the phase and amplitude information of each observable which characterize the participation in each mode, we propose an averaged index of wind power smoothing via KMD, which follows previous investigations of wind power smoothing in Japan [10,11] via PSDs. The performance of the proposed index is exemplified by incorporating large-scale weather simulation data from the Cloud Resolving Storm Simulator (CReSS) [18] to study practical smoothing effects of wind power in Japan.…”
Section: Introductionmentioning
confidence: 99%